The Effectiveness of the Zakat, Infaq and Alms (ZIS) Fund Distribution Program in the Form of Scholarships for Underprivileged Muslim Students by the Amil Zakat Agency National (BAZNAS) Langkat Regency in 2020 - Nurma Hasanah; Imsar Imsar; Suwandi Suwandi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of this study was to determine (1) the effectiveness of the zakat, infaq and alms (ZIS) distribution program in the form of scholarships, (2) the challenges faced in distributing zakat, infaq and alms (ZIS) funds in the program, (3) efforts made in overcoming the attacks of zakat, infaq and alms (ZIS) funds in the scholarship program. Data collection in this study used the method of documentation and semi-structured interviews. The results of this study indicate that the level of effectiveness of the zakat, infaq and alms (ZIS) fund distribution program in the form of scholarships is in the ineffective category, this is because scholarship funds become victim grant funds during the pandemic. Keywords: Effectiveness, scholarships, ZIS